The Program Keluarga Harapan (PKH): For Poverty Reduction and Social Protection - Rahmi Rahmi; ulfia Ulfia (International Conference on Multidisciplinary Research, 2022)
The general objective of Program Keluarga Harapan (PKH) is a program that can increase accessibility to education, health, and social welfare services in supporting the achievement of the quality of life of poor families so that they become more feasible. The PKH is a poverty alleviation program and a social protection system for the poor that aims to support the achievement of development goals, with the support of beneficiaries which has become the goal of the PKH participants. The implementation of the PKH in Aceh Besar Regency is a condition that shows the activities of implementing cash assistance for the poor. So that, what determined beforehand was achieved. PKH is also expected to reduce the burden of spending on poor families in the short term and can also break the poverty chain in the long term in an area. The method used in this study is a qualitative descriptive method. Based on the results, in general, the implementation of the PKH has been going very well. It can be seen from the condition of the recipients of PKH assistance, they used it to help with the social conditions and education of children, help with health and nutrition costs for pregnant women, postpartum mothers, and children under 6 years old from poor households, and make PKH participants aware of the importance of these services. Keywords: implementation, government policy, PKH, poverty, social protection.